2013
DOI: 10.1089/fpd.2013.1492
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-Positive Staphylococci Isolated from Chicken Meat: Pathogenic Potential and Vancomycin Resistance

Abstract: Coagulase-positive staphylococci (CPS) cause staphylococcal food poisoning. Recently, these bacteria have received increasing attention due to their potential role in the dissemination of antibiotic resistance markers. The present study aimed to evaluate coagulase-positive staphylococci counts, species distribution, enterotoxin genes prevalence, and the antibiotic resistance profile of CPS isolated from in natura chicken meat. Fifteen frozen and 15 chilled industrialized, uncooked chicken parts or entire carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
4
25
0
2
Order By: Relevance
“…Staphylococcus are a genre of bacteria widespread in nature, being found in the air, soil, water, food products and animals, including human beings (Faria et al 2009, Hou et al 2012, Martins et al 2013. In this study the frequency to CNS species was higher than CPS, this result agrees with Serapicos (2008) and Faria et al (2009) who also demonstrated an elevated frequency of CNS in wastewater.…”
Section: Resultssupporting
confidence: 87%
“…Staphylococcus are a genre of bacteria widespread in nature, being found in the air, soil, water, food products and animals, including human beings (Faria et al 2009, Hou et al 2012, Martins et al 2013. In this study the frequency to CNS species was higher than CPS, this result agrees with Serapicos (2008) and Faria et al (2009) who also demonstrated an elevated frequency of CNS in wastewater.…”
Section: Resultssupporting
confidence: 87%
“…Antimicrobial resistance was mainly against penicillin (94%), clindamycin (90%), and sulfamethoxazole/trimethoprim (82%). Vancomycin-resistant S. aureus showed intermediate resistance (51%), which might indicate the dissemination of vancomycin resistance in the community and imply food-safety hazards (Martins et al, 2013). The percentage of resistance to b-lactams was variable, with the highest resistance being to penicillin (94%) and lowest to ampicillin-sulbactam (22%).…”
Section: Resultsmentioning
confidence: 99%
“…Coagulase-negative staphylococci (CoNS) , including many species such as S. hyicus [3], S. gallinarum [4], S.xylosus and S. epidermidis [5,6], and commonly been isolated from the nares and skin of healthy chickens, and their taxonomic positions were discussed apart from the pathogenicities. CoNS had been isolated from frozen and chilled industrialized, uncooked chicken parts or entire carcasses [7] , raw chicken's meat [8,9] , meat product [10] , cooked chicken products [11] , breast, neck and wing of chickens [12] , chicken carcasses herd-wise pooled neck skin samples [13] as well as poultry bioaerosol [14] .…”
Section: Introductionmentioning
confidence: 99%